Seasonal undernutrition in rural Ethiopia - Ferro-Luzzi, Anna; Morris, Saul Sutkover; Taffesse, Samson; Demissie, Tsegaye; D'Amato, Maurizio; International Food Policy Research Institute; Istituto Nazionale Della Nutrizione, Rome; Ethiopian Health and Nutrition Research Institute (International Food Policy Research Institute, 2001)
Marked seasonal variability of both production- and consumption is characteristic of virtually all farming systems in the developing world. This study examines the magnitude and significance of seasonal undernutrition in south central Ethiopia, southern Shewa and Zigwa Boto, a peasant association in the Gurage Zone. The study seeks to answer five questions: (1)Does seasonal energy stress affect individuals of various age groups and sexes differently?; (2)Do members of the same household show divergent responses to seasonal energy stress?; (3)What are the functional consequences of different levels of adult undernutrition?; (4)Are the current anthropometric cut-off points for adults appropriate for rural Ethiopia?; (5)What household characteristics are associated with vulnerability to seasonal undernutrition?; A number of important findings emerge from this research.....The study clarifies some points of contention in the field of adult undernutrition and shows how seasonal undernutrition operates as an intermittent warning signal, reminding us not to miss opportunities to promote good nutrition throughout the life cycle.